Integrating English Language Instruction Into Vocational Artisan Training: A Framework for Enhanced Professional Competence and Economic Empowerment in Nigeria - Obera, Joy Aladi; Gunawan, Resky Nuralisa; Momoh, Muazu Adamu; Omachonu, Gowon Clement; Ojochegbe, Ameh Timothy (International Journal of Social Service and Research, 2025)
This research investigates the integration of English language instruction into Nigerian vocational artisan training programs to enhance communicative competence, professional performance, and economic inclusion among tradespeople. Grounded in English for Specific Purposes (ESP) theory and workplace literacy frameworks, the study employed a mixed-methods research design, combining structured surveys with semi-structured interviews. A total of 63 artisans across five trades—carpentry, tailoring, welding, automotive repair, and electrical installation—participated in the study conducted in Kogi State, Nigeria. Quantitative findings revealed critically low English proficiency levels, with only 12.4% of respondents demonstrating high proficiency in reading technical documents and 10.0% in writing estimates and invoices. Communication-related challenges occurred frequently in workplace contexts, with misunderstanding client requests (M = 3.31) and inability to interpret safety instructions (M = 3.25) emerging as the most prevalent issues. Qualitative data identified specific trade-based English needs, including reading technical manuals, writing job quotations, using digital marketing platforms, and understanding safety regulations. Based on these findings, the study proposes a Trade-Specific English Curriculum (TSEC) framework designed to integrate task-based language instruction with authentic workplace demands through five interconnected components: Needs Analysis, Task-Based Modules, Authentic Materials, Collaborative Learning, and Performance-Based Assessment. The study concludes that language integration within vocational programs represents both a pedagogical and economic imperative, with implications for workforce competitiveness, occupational safety, and formal economic participation. The proposed framework offers a replicable model for vocational education reform aligned with Nigeria’s sustainable development objectives.